Pemahaman Konsep Fisika Calon Guru Biologi Pada Topik Kinematika - Dios Sarkity; Putri Dwi Sundari (Pedagogi Hayati, 2020)
Physics is closely related to problem solving. To be able to solve the problem appropriately, it takes a good conceptual understanding to analyze the concepts underlying the problem and to determine the correct problem-solving procedure based on the condition of the problem. Poor conceptual understanding causes the inability of students to solve various physics problems. Kinematics is a fundamental concept in physics that is needed to understand other physics concepts. As a biology teacher candidate, a biology education student is required to master other science fields such as physics. Therefore, the authors tested the physics conceptual understanding of biology teacher candidates on the topic of kinematics. The purpose of this study was to determine the physics conceptual understanding possessed by biology teacher candidates on the topic of kinematics. This research was a descriptive study with data collection techniques using questionnaires in the form of essay questions to test students' conceptual understanding regarding distance and displacement, velocity and acceleration. The results showed that there were still problems for biology teacher candidates in understanding the concepts of distance, displacement, velocity and acceleration. Therefore, a lecture method is needed that can improve the physics conceptual understanding of biology teacher candidates through general physics courses.